1982
DOI: 10.1002/pol.1982.170200615
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl polymerization by lithium organocuprates

Abstract: Vinyl polymerizations initiated by lithium organocuprates under several conditions were investigated. It was observed that this catalyst was effective in the polymerization of specific monomers such as α,β‐unsaturated nitrile and carbonyl analogues. The rate of polymerization was rapid but retarded by the addition of pyridine, nitrobenzene, or hydroquinone. Polymerization of methyl methacrylate (MMA) with lithium di‐n‐butylcuprate as initiator produces predominantly isotactic poly(methyl methacrylate) (PMMA) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…28 Anionic polymerisation of MMA initiated by cuprate reagent resulted in highly syndiotactic materials when the experiments were conducted in polar solvent, 29 and predominantly isotactic in toluene. 30 In the course of our studies concerning the valorisation of lanthanide borohydrides for polymerisation, 10 times higher), denoting that only a small percentage of the catalyst had initiated the reaction. However, these preliminary results were considered motivating since a significant control of the tacticity (rr 76 %) was observed, in sharp contrast with the conventional, aspecific, radical polymerisation of MMA.…”
Section: Introductionmentioning
confidence: 90%
“…28 Anionic polymerisation of MMA initiated by cuprate reagent resulted in highly syndiotactic materials when the experiments were conducted in polar solvent, 29 and predominantly isotactic in toluene. 30 In the course of our studies concerning the valorisation of lanthanide borohydrides for polymerisation, 10 times higher), denoting that only a small percentage of the catalyst had initiated the reaction. However, these preliminary results were considered motivating since a significant control of the tacticity (rr 76 %) was observed, in sharp contrast with the conventional, aspecific, radical polymerisation of MMA.…”
Section: Introductionmentioning
confidence: 90%
“…Given the possibility of living polymerization of alkyl (meth)acrylate under mild conditions, lithium organocuprates ([R 2 Cu] − Li + ), also known as Gilman reagents, have been used as anionic initiators35–39 because they favor 1,4‐addition reactions and behave with high regio‐ and stereoselectivity when reacted with various α,β‐unsaturated esters and ketones. Gregonis was the first to prepared stereoregular poly(hydroxyethyl methacrylate) with Bu 2 CuLi in toluene 35.…”
Section: Introductionmentioning
confidence: 99%
“…Gregonis was the first to prepared stereoregular poly(hydroxyethyl methacrylate) with Bu 2 CuLi in toluene 35. Han synthesized stereoregular poly(methyl methacrylate)(PMMA) using the same initiator 36. Kawaguchi prepared poly(tert‐butyl methacrylate) (PTBMA) and PTBMA‐b‐PMMA with Me 2 CuLi39 and polymerization was proven to be partially living 37, 39.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 It was shown by Grigonis et al 8 that benzoxyethyl methacrylate polymerization initiated with lithium din-butylcuprate ((n-Bu)zCuLi) in toluene affords highly isotactic polymers (5% syndiotactic, 15% heterotactic, and 80% isotactic triad contents). Han et al 9 reported (n-Bu) 2 CuLi to be an effective initiator for O!,/J-unsaturated monomers, MMA, acrylonitrile, acrolein, and Nacryloylpyrrolidone to afford highly isotactic polymers in toluene. They, however, did not report any evidence related to the molecular weight distribution (MWD) of the polymers and the possibility that the reaction may proceed in a living manner.…”
mentioning
confidence: 99%